Microhistories of composition - McComiskey, Bruce, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
Writing studies has been dominated throughout its history by grand narratives of the discipline, but in this volume Bruce McComiskey begins to explore microhistory as a way to understand, enrich, and complicate how the field relates to its past. Microhistory investigates the dialectical interaction of social history and cultural history, enabling historians to examine uncommon sites, objects, and agents of historical significance overlooked by social history and restricted to local effects by cultural history. This approach to historical scholarship is ideally suited for exploring the complexities of a discipline like composition. Through an introduction and eleven chapters, McComiskey and his contributors--including major figures in the historical research of writing studies, such as Louise Wetherbee Phelps, Kelly Ritter, and Neal Lerner--develop focused narratives of particular significant moments or themes in disciplinary history. They introduce microhistorical methodologies and illustrate their application and value for composition historians, contributing to the complexity and adding momentum to the emerging trend within writing studies toward a richer reading of the field's past and future. Scholars and historians of both composition and rhetoric will appreciate the fresh perspectives on institutional and disciplinary histories and larger issues of rhetorical agency and engagement enacted in writing classrooms that are found in Microhistories of Composition. Other contributors include Cheryl E. Ball, Suzanne Bordelon, Jacob Craig, Matt Davis, Douglas Eyman, Brian Gogan, David Gold, Christine Martorana, Bruce McComiskey, Josh Mehler, Annie S. Mendenhall, Kendra Mitchell, Antony N. Ricks, David Stock, Kathleen Blake Yancey, Bret Zawilski, and James T. Zebroski.--Provided by publisher.
At a Hinge of History in 1963: Rereading Disciplinary Origins in Composition / Annie S. Mendenhall -- The 1979 Ottowa Conference and Its Inscriptions: Phelps A Canadian Moment in American Rhetoric and Composition / Louise Wetherbee Phelps -- Journal Editors in the Archives: Reportage as Microhistory / Kelly Ritter -- History of a Broken Thing: The Multi-Journal Special Issue on Electronic Publication / Cheryl E. Ball and Douglas Eyman -- "Bodily Pedagogies" and the Act of Reading: Women's Rhetorical Education and the School of Expression at the Turn of the Twentieth Century / Suzanne Bordelon -- Teaching Grammar to Improve Student Writing?: Revisiting the Bateman-Zidonis Report of 1966 / James T. Zebroski -- Who Was Warren Taylor?: A Microhistorical Footnote to Berlin's Rhetoric and Reality / David Stock -- Remembering Roger Garrison: Composition Studies and the Star-Making Machine / Neal Lerner -- Elizabeth Ervin and the Problems of Civic Engagement: A Composition Teacher's Struggle to Teach Public Argument / David Gold -- Going Public with Ken Macrorie / Brian Gogan -- Against the Rhetoric and Composition Christine Martorana, Grain: A Microhistorical View / Jacob Craig, Matt Davis, Josh Mehler, Kendra Mitchell, Antony N. Ricks, Bret Zawilski, and Kathleen Blake Yancey.
Keywords: Microhistory; Historiography